On the Fresnel integrals and the convolution - Kiliçman, Adem; Fisher, Brian (Hindawi Publishing, 2003)
The Fresnel cosine integral C (x), the Fresnel sine integral S (x), and the associated functions C+ (x), C- (x), S+ (x), and S- (x) are defined as locally summable functions on the real line. Some convolutions and neutrix convolutions of the Fresnel cosine integral and its associated functions with x+r and xr are evaluated.